The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0735-1097(00)00785-3
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous isosorbide-dinitrate is safer and better than Bi-PAP ventilation combined with conventional treatment for severe pulmonary edema

Abstract: High dose ISDN is safer and better than BiPAP ventilation combined with conventional therapy in patients with severe pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
3
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 10 publications
1
134
3
6
Order By: Relevance
“…In the first one 202 , NIV was compared with the use of high doses of nitrates. The study was interrupted early because of the excessive number of adverse events and reduced efficacy in the NIV arm.…”
Section: F Acute Pulmonary Edema (Table 26)mentioning
confidence: 99%
“…In the first one 202 , NIV was compared with the use of high doses of nitrates. The study was interrupted early because of the excessive number of adverse events and reduced efficacy in the NIV arm.…”
Section: F Acute Pulmonary Edema (Table 26)mentioning
confidence: 99%
“…In another nitrate trial, 40 patients were randomized to receive 4 mg ISDN every 4 min or bi-level positive airway pressure (BiPAP) plus a standard-dose ISDN infusion starting at 10 μmol/min and increased every 5-10 min, which is considered a conventional treatment. The researchers found a lower mortality rate (0% compared with 40%) in the 4 mg ISDN group, less need for mechanical ventilation (20% compared with 80%), and a lower incidence of MI (10% compared with 55%) (19). Recently, Breidthardt showed that sublingual and transdermal nitrates had an improving effect on the mortality in patients with acute HF.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial of 110 patients comparing high‐ versus low‐dose nitrates, Cotter et al reported that there was no difference in mortality rates, although there were only 4 deaths in total during the study 24. Sharon and colleagues randomized 40 patients with severe pulmonary edema to either intravenous nitrates or noninvasive positive pressure ventilation and demonstrated a reduction in the composite end point of death, myocardial infarction, or mechanical ventilation in the intravenous nitrate group 13. However, the study was terminated prematurely and a total of 2 deaths occurred during the study, limiting its inference in relation to survival benefit.…”
Section: Discussionmentioning
confidence: 99%